EFEKTIVITAS EKSTRAK KULIT BATANG AMPUPU (Eucalyptus alba Reinw. Ex. Blume) DALAM MENGHAMBAT PERTUMBUHAN JAMUR Fusarium sp. PENYEBAB BUSUK TONGKOL JAGUNG (Zea mays L.) - Metboki, Bernadina; Astiti, Ni Putu Adriani; Proborini, Meitini Wahyuni (Metamorfosa: Journal of Biological Sciences; Vol 3 No 2 (2016)DO - 10.24843/metamorfosa.2016.v03.i02.p01, 2016)
The fungal-related diseases were responsible as one of many reasons for low production of maize in Indonesia. Controlling fungal contaminants using chemical is hazardous for human nowadays. Thus the need of environmental friendly vegetative-based fungicide such as from the extract of Ampupu tree bark is important. The objective of this study was to investigate the antifungal effect from Ampupu tree bark crude extract in response to growth of Fusarium sp , which responsible as the causal agent of corncob rot. The inhibition test on growth of Fusarium sp. by Ampupu tree bark crude extract was performed with diffusion well method on PDA as media. The process involved the infusion of crude extracts at 1.5%, 3.0% and 4.5% concentration, respectively, into diffusion well on each Petri disk. The result showed that by in vivo treatment, crude extract of Ampupu tree bark with concentration of 1.5%, 3,0% and 4.5%, were able to inhibit the fungal growth of Fusarium miniliforme as the causal agent of corncob rot with diameter of inhibition zone 0.18 mm, 1.85 mm and 2.01 mm, respectively. The higher the concentration of the crude extract given, the larger the diameter of inhibition zone formed.
Keywords: antifungal activity, Ampupu tree’s teaks, Fusarium moniliforme